THE MOLECULAR BASIS OF RESISTANCE ANTIRETROVIRAL MARKERS AND POLYMORPHISMS OF THE HUMAN IMMUNODEFICIENCY VIRUS-1 SUBTYPE CRF01-AE PROTEASE GENE IN NAÏVE AND TREATMENT FAILURE PATIENTS IN BALI - Sri Budiyanti, N.; Suata, I K.; Merati, K. T. P.; Mahardika, I G.N.K. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
ABSTRACT Application of antiretrovirals (ARVs) in patients with Human Immunodeficiency Virus (HIV) infection has proven to reduce mortality rates and prolong life expectancy. On the other hand, the use of antiretroviral drugs has incited the emergence of HIVDR. The resistance is due to mutation at genes associated with drug resistance. Nowadays, the determination of resistance markers mutations are based on HIV-1 subtype B. However, the majority of HIV in Indonesia, particularly in Bali are of subtype CRF01_AE. Genetic variation between HIV viruses has led to variations in subtypes; therefore, resistance markers of subtype B could be polymorphisms of non-B subtypes. This study aims to determine the number and types of the resistance markers mutations and polymorphisms that occur on the PR gene of HIV-1 subtype CRF01_AE of naïve and treatment failure patients in Bali. This is an observational cross-sectional analytical study, conducted at two VCT clinics in Denpasar, during the period of April 2010 until October 2011. Samples consist of 18 HIV patients with treatment failure and 30 naïve HIV patients. Mutations were evaluated using PCR, sequenced and aligned were carried out using MEGA4. Interpretations of the mutations were made based on the Stanford HIV database. Hypothesis tests used were Mann-Whitney because of abnormal distribution of data. Hypothesis was accepted if the significant level p<0.05. This study found that of the demographic data, only the predisposing factors of the two groups were significantly different (p<0.05). Two patients with treatment failure and 5 naïve patients were found to have L10LV/I mutations. Only one patient with treatment failure had the I54FI mutation. No major mutations were found among the two study groups. The number and types of minor mutations were not significantly different (p>0.05) between the naïve group and treatment failure group. M36I and H69K polymorphisms of the PR gene were found in all the study samples. In conclusion of this study, two types of major mutations were found, L10LV/I and I54FI. The number and types of the resistance markers mutations towards the protease inhibitor (PI) group were not significantly different between the two study groups. M36I, H69K mutations of the PR gene are markers of polymorphisms of HIV-1 subtype CRF01_AE.